Pengembangan Model Pelatihan Berbasis Kinerja bagi Peningkatan Kompetensi Pimpinan Perusahaan Startup - Arie Indra Gunawan; Wahyu Rafdinal; Fatya Alty Amalia; Nugroho Hardiyanto; Dedy Saefuloh (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2020)
AbstractThis research develops a performance-based training management model to produce start-up companies that have superior competitiveness in their independence and business development. Using the Research & Development approach, this research uses a locus of start-up companies in Bandung. Research subjects are the leaders or business owners of start-up companies. The managerial training and development model that is often based on various studies is concluded to run with various deficiencies in every aspect, starting from the planning, implementation, and results obtained. Based on this, the reconstruction of training and development models is carried out by examining the factors that are relevant for managerial training and development, especially in start-up companies. The results of our study show that the performance-based training model developed for managerial training and development has proven to be effective in increasing the competencies of leaders and owners of start-up companies in Bandung. Keywords: Training management model, Competencies, Performance, Business owners of start-up companies.